Clima laboral de la Tienda Tropimotors, sucursal de Babahoyo - Junco Garrido, Nathaly Carla (2021)
The work environment is one of the most important aspects of the company, we can define it as a series of social and psychological conditions that represent the characteristics of the organization and directly affect the performance of employees. Therefore, when the work environment allows people to develop and increase their confidence, it is appropriate; In addition to motivating them to develop emotions, it also improves the satisfaction and commitment of employees with the institution during the development of activities. Within the organization, there must be an orderly environment to properly guide and motivate each member, and to cultivate positive employees. The present case study called “Labor Climate of the Tropimotors store, Babahoyo branch” set out as an objective to identify how the working climate affects the employees of the business; as well as analyzing the direct effect it has when carrying out daily tasks in the different areas, the performance of its employees and the productivity of the company. The existing problems in the Tropimotors store, Babahoyo branch, were raised based on the work environment, the same that are evident in the development. The descriptive and analytical research methods which allowed obtaining the necessary information, the techniques and instruments used to collect information were: an interview and surveys, which helped in obtaining results that allowed to reach a general conclusion of the present case study, the same one that was supported by bibliographic references that helped to understand the depth of this research.